High-performance layered potassium vanadium oxide for K-ion batteries enabled by reduced long-range structural order. Issue 22 (24th May 2021) - Niu, Xiaogang; Qu, Jiale; Hong, Youran; Deng, Leqing; Wang, Ruiting; Feng, Meiying; Wang, Jiangwei; Zeng, Liang; Zhang, Qianfan; Guo, Lin; Zhu, Yujie
Abstract : The capacity degradation mechanism of layered potassium vanadium oxide K0.5 V2 O5 towards K-ion storage was unveiled and the cycling stability of this material was enhanced by reducing its long-range structural order. Abstract : Potassium ion batteries (KIBs) are attracting increasing research interest as a potential low-cost energy storage system. Currently, the development of KIBs is mainly hindered by the poor cycle life of cathode materials, caused by the large K-ion-induced mechanical failure during charge–discharge. Herein, taking layered K0.5 V2 O5 as an example, we show that reducing the long-range structural order is an effective way to boost its K-ion storage performance. The obtained nanocrystalline K0.5 V2 O5 ·0.5H2 O is capable of retaining 81% of its capacity after 200 cycles, outperforming its highly crystalline counterpart which only exhibits 33.3% capacity retention after 100 cycles. Detailed spectroscopic and electrochemical characterization techniques indicate that the charge storage mechanism is changed from battery-type intercalation accompanied by phase transition in the highly crystalline K0.5 V2 O5 to phase transition-free pseudocapacitive K-ion intercalation in the nanocrystalline K0.5 V2 O5 ·0.5H2 O. Theoretical calculations further suggest that the interlayered water plays a critical role in suppressing the phase transition which mitigates the mechanical damage of the nanocrystalline sample, leading to its enhanced cycling stability. The present work will provide new insights to improve the cycling stability of other electrode materials for KIBs.